Toxicity of Cipadessa fruticosa to the leaf-cutting ants Atta sexdens rubropilosa (Hymenoptera: Formicidae) and their symbiotic fungus - Leite, Ana C.; Oliveira, Cintia G. [UNESP]; Godoy, Marizete P. [UNESP]; Bueno, Fabiana C. [UNESP]; De Oliveira, M. de Fátima S. Dos S. [UNESP]; Forim, Moacir R.; Fernandes, João B.; Vieira, Paulo C.; Da Silva, M. Fátima Das G.F.; Bueno, Odair C. [UNESP]; Pagnocca, Fernando C. [UNESP]; Hebling, M. José A. [UNESP]; et al. (My University, 2005)
Crude extracts from fruits, branches and leaves of Cipadessa fruticosa were assayed on Atta sexdens rubropilosa workers and their symbiotic fungus Leucoagaricus gongylophorus. The results showed that the majority of the extract tested reduced significantly (p < 0.05) the survival of the workers comparable to the neem oil. In addition, the dichloromethane extract from fruits and the hexane extract from branches of C. fruticosa inhibited in 80% the development of the symbiotic fungus. The hexane and dichloromethane extracts from fruits of C. fruticosa were fractionated and their fractions were subjected to new bioassays. Several fractions showed relevant activity on ants, but none of them inhibited significantly the fungal growth. The possibility of controlling leaf-cutting ants in the future using C. fruticosa is discussed.
Keywords: Anti-fungal activity; Atta sexdens rubropilosa; Cipadessa fruticosa; Leaf-cutting ants; Leucoagaricus gongylophorus; Meliaceae; Atta; Azadirachta indica; Cipadessa; Formicidae; Fungi; Hymenoptera